The Relationship Between PUS Knowledge And Husband's Support In Choosing The IUD Contraception Method - Sholikah, Siti Mar’atus; Islamiah, Ahdatul; Aini, Elfira Nurul (Universitas Tribhuwana Tunggadewi, 2024)
IUD is highly affective non-hormonal contraceptives. This research aims to analyze the relationship between the knowledge of PUS and husband's support with the choice of IUD contraception at the Senori Tuban Community Health Center. This research is a cross sectional correlational analytic study, involving 61 respondents selected through a stratified random sampling technique. The independent variable is knowledge of PUS and the husband's support, while the dependent variable is the choice of the IUD contraceptive method. Data were collected using a questionnaire and checklist, and the relationship was analyzed using the chi square test with a significance level of α 0.05. The results showed that most 32 (52.5%) couples had good knowledge about IUD contraception, most 35 (57.4%) husbands provided support, and 35 (57.4%) couples chose the IUD as their contraception method. The analysis concluded a significant relationship between the knowledge of PUS and the husband's support with the choice of IUD contraception. It is recommended that husbands provide positive support to their wives who are KB acceptors. Additionally, they are encouraged to actively seek reliable information directly to health care providers or other sources about their family planning.